Сили спеціальних операцій Сухопутних військ Франції - Слюсаренко, Андрій; Slyusarenko, Andriy (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті схарактеризовано організаційну модель сил Спеціальних операцій Сухопутних військ (ССО СВ) Франції. Визначено основні частини й підрозділи її ССО СВ. Узагальнено структуру та завдання, які покладено на частини й підрозділи ССО СВ. Наведено склад Командування спеціальних операцій (КСО). Проаналізовано організацію функціонування КСО, визначено основні напрями його дій, наведено відмінності щодо організації управління частинами та підрозділами ССО СВ Франції, США, Великої Британії. In the article, on the basis of analysis, published documents and specialized literature, a scientific reconstruction of the conceptual organizational and functional model of Special Operations Forces in France was carried out. The organizational model of the Special Operations Forces of France is disclosed, the main parts and units are listed. The structure and task of these troops in France is disclosed, the main parts and units are listed. The structure and tasks that are assigned to the units and subdivisions of the Special Operations Forces are described. The composition of the Command of special operations is given. The organization and functioning of Special Operations Forces is analyzed, the main directions of its actions are determined, and the differences in the organization of management of units and divisions of the Special Operations Forces of France, the USA, and Great Britain are shown. The experience of reforming the Special Operations Forces of France will not only allow us to choose the most effective model of development, but also to choose the most effective model for managing our own Special Operations Forces.
French Army Special Operations Forces
Keywords: Сили спеціальних операцій; спеціальна операція; Special Operations Forces; special operation